2015
DOI: 10.1111/jfs.12202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet‐C Radiation Combined with Unconventional Atmosphere Packaging on the Quality of Fresh‐Cut Arugula (Eruca Sativa Mill.)

Abstract: The combined effects of ultraviolet (UV) light C (0.34 to 20.13 kJ/l2) and superatmospheric O2 (>85%) packaging on the respiration rate, atmospheric composition, microbiological growth and nutritional quality of fresh‐cut arugula stored for 10 days at 5C were studied. All treatments performed under increased O2 levels exhibited a reduction in the respiration rate throughout the cold storage. High microbial load of the raw material were found. UV‐C radiation enabled an initial reduction of about 1 and 1.5 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Arugula has become an increasingly popular worldwide vegetable (Cernava et al, 2019; Mallah et al, 2017). Arugula leaf is a good source of vitamin A and C (Silveira Gómez, Baeza Ramírez, & Escalona Contreras, 2015), vital antioxidants (Melchini & Traka, 2010), glucosinolates, and flavonols (Bell & Wagstaff, 2014; Michael, Shafik, & Rasmy, 2011), potassium, sulfur, and fiber (Kawashima & Soares, 2003; Nunes et al, 2013). In addition to consumption as a food ingredient and sauce (Tassi et al, 2018), arugula is widely cultivated as green manure (Abdi, Tajbakhsh, Mandulakani, & Sadaghiani, 2013; Javadi, Rezvani Moghaddam, Rashed, & Seghatoleslami, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Arugula has become an increasingly popular worldwide vegetable (Cernava et al, 2019; Mallah et al, 2017). Arugula leaf is a good source of vitamin A and C (Silveira Gómez, Baeza Ramírez, & Escalona Contreras, 2015), vital antioxidants (Melchini & Traka, 2010), glucosinolates, and flavonols (Bell & Wagstaff, 2014; Michael, Shafik, & Rasmy, 2011), potassium, sulfur, and fiber (Kawashima & Soares, 2003; Nunes et al, 2013). In addition to consumption as a food ingredient and sauce (Tassi et al, 2018), arugula is widely cultivated as green manure (Abdi, Tajbakhsh, Mandulakani, & Sadaghiani, 2013; Javadi, Rezvani Moghaddam, Rashed, & Seghatoleslami, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This trend agrees with the results observed in the present investigation. Many authors have attributed this stabilization to tissue's mechanisms of response by UV‐C stress, that involves the induction of enzymes linked to the biosynthesis of polyphenols (Lemoine et al, 2010; Silveira et al, 2015; Strack, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The following hurdles are used commonly along with UV light to overcome the limitations of the treatment: mild heat (George et al, 2015;Sew et al, 2014), visible light (Falguera et al, 2013), sonication (Caminiti et al, 2011;Santhirasegaram et al, 2015), pulsed electric field (Noci et al, 2008), ozone (Dev Kumar et al, 2016), anti-microbial agents (Chun & Song, 2014;Lee et al, 2012), packaging techniques (Maghoumi et al, 2013;Morris et al, 2007;Silveira et al, 2015), and storage conditions (Pala & Toklucu, 2013). Using hurdle technology, these authors have reported increased microbial inactivation and improved quality attributes in terms of physicochemical, sensory and nutritional quality.…”
Section: Hurdle/combination Technologiesmentioning
confidence: 99%